Comparison Between Intravitreal Triamcinolone Acetonide and Posterior Sub-Tenon’s Injection in Treating Diabetic Macular Edema - HAMMAD SARWAR ZAMIR IQBAL, JAWWAD AHMAD (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the efficacy of intra-vitreal versus sub Tenon triamcinolone acetonide administration in treatment of Diabetic Macular Edema(DME). Patients and Methods: This prospective clinical, pilot study was conducted at the Armed Forces Institute of Opthalmology, Rawalpindi from January 2011-April 2011. 12 patients 6 in each group were recruited at AFIO Rawalpindi, 6 underwent IVTA and the other 6 PSTI, Macular thickness and visual acuity were checked at baseline 01 and at 03 months and IOP was measured at baseline at 2 weeks. Results: There was no statistical difference between the efficacy of either modality. Both groups showed a statistically significant decrease in Macular thickness, improvement in visual acuity and maintenance of IOP. Conclusions: PSTI can be explored as a viable alternative to IVTA with reduced side effects.